PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERJUDIAN SABUNG AYAM (STUDI PADA KEPOLISIAN RESOR KOTA BARELANG) - Pais, Syahdan; Arman, S.H., M.H., Zuhdi (SCIENTIA JOURNAL, 2021)
Gambling is pure chance speculation, deliberate betting, namely risking one value or something that is considered valuable by realizing certain risks and expectations at game events, matches, competitions and events that have no certain outcome. Whereas Cockfighting or a game of connecting chickens, also known as cock-fighting, is a game of fighting two chickens in an arena or arena. Usually the chickens are pitted until one of them runs away or loses, even to death. The purpose of this study was to determine how the law enforcement process is and what are the efforts and barriers to law enforcement against the crime of cockfighting gambling in the jurisdiction of Batam City. The research method used is Empirical, data collection methods are carried out by interviews, observation and documentation The results of this study indicate that law enforcement against perpetrators of cockfighting gambling has been prosecuted based on the provisions of the applicable laws and the efforts of law enforcers to enforce the applicable laws are preventive and repressive measures.